Recent and Upcoming Drug Therapies for Pediatric Heart Failure - Loss, Karla L.; Shaddy, Robert E.; Kantor, Paul F. (Frontiers in Pediatrics, 2021)
Pediatric heart failure (HF) is an important clinical condition with high morbidity, mortality and costs. Due to the heterogeneity in clinical presentation and etiologies, the development of therapeutic strategies is more challenging in children than adults. Most guidelines recommending drug therapy for pediatric HF are extrapolated from studies in adults. Unfortunately, even using all available treatment, progression to cardiac transplantation is common. The development of prospective clinical trials in the pediatric population has significant obstacles, including small sample sizes, slow recruitment rates, challenging endpoints and high costs. However, progress is being made as evidenced by the recent introduction of ivabradine and of sacubitril/valsartan. In the last 5 years, new drugs have also been developed for HF with reduced ejection fraction (HFrEF) in adults. The use of well-designed prospective clinical trials will be fundamental in the evaluation of safety and efficacy of these new drugs on the pediatric population. The aim of this article is to review the clinical presentation and management of acute and chronic pediatric heart failure, focusing on systolic dysfunction in patients with biventricular circulation and a systemic left ventricle. We discuss the drugs recently approved for children and those emerging, or in use for adults with HFrEF.